Development and Characterization of Carob Flour Based Functional Spread for Increasing Use as Nutritious Snack for Children - Sema Aydın; Yüksel Özdemir (Journal of Food Quality)
Carob flour enriched functional spread was developed and textural, sensory, colour, and some nutritional properties of the product were investigated. Spread samples were prepared with major ingredients for optimisation and minor ingredients for improving texture and aroma. Major ingredients were carob flour and hydrogenated palm oil (HPO) and minor ingredients were commercial skim milk powder, soya flour, lecithin, and hazelnut puree. The ratio of major ingredients was optimised using sensory scores and instrumental texture values to produce a carob spread that most closely resembles commercial chocolate spread (control), in both spreadability and overall acceptability. The amounts of minor ingredients (milk powder, 10%; soybean flour, 5%; lecithin, 1%; hazelnut puree, 4%) were kept in constant ratio (20%). Addition of hydrogenated palm oil (HPO) decreased the hardness and hardness work done (HWD) values in contrast to carob flour. Higher rates of carob flour were linked to lower lightness, greenness, and yellowness values. Spread was optimised at 38 g carob flour/100 g spread and 42 g hydrogenated palm oil/100 g spread level and the formulation tended to receive the highest sensory scores compared to other spreads and presented closer instrumental spreadability values to control samples. This indicates a strong market potential for optimised carob spreads.